Maximum entropy modeling for the conservation of Hopea odorata in riparian forests, central Thailand - LAMTHAI ASANOK; TORLARP KAMYO; DOKRAK MAROD (Society for Indonesian Biodiversity, 2020)
Abstract. Asanok L, Kamyo T, Marod D. 2020. Maximum entropy modeling for the conservation of Hopea odorata in riparian forests, central Thailand. Biodiversitas 21: 4663-4670. Hopea odorata plays a dominant role in both ecologically and economically in Thailand. We analyzed potentially suitable areas for H. odorata in the riparian zone of the Chao Phraya River using the software MaxEnt. Modeling included 164 occurrence records along with 19 climate-related variables, slope, aspect, and elevation. Precipitation was the key climatic variable influencing the distribution of H. odorata. Riparian areas along the Chao Phraya that were predicted to be highly suitable for this species were located in the provinces of Nakhon Sawan, Ang Thong, Phra Nakhon Si Ayutthaya, Pathum Thani, Nonthaburi, and Bangkok. The ROC AUC score was 0.891, indicating that MaxEnt is an excellent tool for predicting suitable regions for the restoration or cultivation of commercially and ecologically valuable species such as H. odorata. Models such as what we have presented here can facilitate habitat conservation and sustainable resource use for rare and important plants.